(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
This comprehensive study explores the intricate dimensions of global health, focusing on the humanitarian response to conflicts and disasters. It grapples with the evolving definition of global health in the 21st century. Emphasizing the shift from the disease-centric approaches to holistic well-being. Rooted in the principles laid by pioneers like William Farr and Rudolf Virchow. Global health now prioritizes evidence-based decision-making, population-centric focus, social justice, and preventive care. This narrative will help to distinguish global health from public health and international health, highlighting its transnational focus on disparities and cross-border issues. The discourse extends to the interconnected determinants of health, encompassing genetics, access to services, and governmental interventions. This paper will underscore the collaborative effort required from various global actors, including UN agencies, foundations, and NGOs. Delving into humanitarian response, this study elucidates the principles of humanity, impartiality, neutrality, and independence that guide modern humanitarian work. Historical cases, such as the Rwandan genocide, underscore the necessity of standardized humanitarian practices exemplified by the Sphere Handbook. The analysis traces the professionalization of humanitarian assistance post-Goma; emphasizing the importance of anticipatory planning and coordination. Finally, this article explores the link between health and broader societal aspects, exemplified by the recent global response to COVID-19. It concludes with a call for continued recognition, application, and research in humanitarian response, guided by leading physicians dedicated to alleviating global suffering within the realm of a robust and interconnected global health framework.